Preparation and electrochemical properties of Li6La3Zr0.7Ti0.3Ta0.5Sb0.5O12 high-entropy Li-garnet solid electrolyte - Ye, Ruijie; Ting, Yin-Ying; Dashjav, Enkhtsetseg; Ma, Qianli; Taminato, Sou; Mori, Daisuke; Imanishi, Nobuyuki; Kowalski, Piotr M.; Eikerling, Michael H.; Kaghazchi, Payam; Finsterbusch, Martin; Guillon, Olivier (Frontiers in Energy Research, 2024)
Garnet-type solid electrolytes stand out as promising Li-ion conductors for the next-generation batteries. It has been demonstrated that the inherent properties of garnets can be tailored by introducing various dopants into their crystal structures. Recently, there has been a growing interest in the concept of high entropy stabilization for materials design. In this study, we synthesized highentropy garnets denoted as Li6La3Zr0.7Ti0.3Ta0.5Sb0.5O12 (LLZTTSO), wherein Ti, Sb, and Ta occupy the Zr site. The formation of the cubic garnet phase in LLZTTSO was confirmed through X-ray diffraction (XRD), and the resulting lattice parameter agreed with predictions made using computational methods. Despite the substantial porosity (relative density 80.6%) attributed to the low sintering temperature, LLZTTSO exhibits a bulk ionic conductivity of 0.099 mS cm -1 at 25°C, and a total ionic conductivity of 0.088 mS cm -1 , accompanied by an activation energy of 0.497 eV. Furthermore, LLZTTSO demonstrates a critical current density of 0.275 mA cm -2 at 25°C, showcasing its potential even without any interfacial modification.